EFEKTIVITAS PENGGUNAAN METODE JARIMATIKA TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DITINJAU DARI JENIS KELAMIN - Dewita Nurmaulani; Erfan Ramadhani; Arief Kuswidyanarko (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This research is motivated by conditions in the field which are still low in mathematics learning achievement for third grade students at SD Negeri 068 Palembang. This is based on observations that have been made where students have difficulty in solving problems related to arithmetic operations. The purpose of this study was to determine the effectiveness of the Jarimatika method on students' mathematical creative thinking skills in terms of the gender of the 3rd grade students of SD Negeri 068 Palembang. This research uses experimental research with One-Group Pretest-Posttest Design. The population of this research is the third grade students of SD Negeri 68 Palembang. The research sample is class III students. A SD Negeri 68 Palembang using non-probability sampling technique. Methods of data collection using observation, tests, and documentation. The results of this study have differences in the Jarimatika method on the mathematical creative thinking ability of third grade students at SDN 068 Palembang. The results shown from the research students answered questions creatively according to students' understanding. There are differences in the creative thinking abilities of male and female students. It is proven by the results on the test questions for male students with a score of 91 and female students with a score of 85. In a sense, male students are superior to female students. The results of this study are also used to see the effectiveness of the Jarimatika method on the ability to think creatively.